Dental Education: Restorative dentistry in Malaysia (Bangladesh Journal of Medical Science, 2013)
Objectives: The aim of this study was to identify the requirements in restorative dentistry that undergraduate dental students have to fulfill in order to sit for final examinations in dental schools in Malaysia and to compare those requirement with the competencies stipulated by the Malaysian Qualification Agency (MQA). Materials and Methods: Questionnaire from a study done previously was modified and used in this study. All questionnaires were sent by post with a reply envelope. Eight dental schools had responded (72%) to the survey and the results showed that although dental schools may differ in the number of numerical requirements, their assessments were quite similar. One school does not practice numerical requirements at all. Results: In term of requirement for full crown, majority of the schools (88%) agreed that porcelain bonded to metal crown should be included in the numerical requirement. In contrast, majority of the schools (88%) did not include inlay/onlay in their numerical requirements. For plastic restorations like composite resin, amalgam and glass ionomer, majority of the schools (88%) used numerical requirements. Majority of the schools also agreed on numerical requirements for conventional bridge (88%) and incisor to molar endodontics (88%), but not for resin bonded bridge (75%). Conclusion: This study shows that there is a disparity among institutions in Malaysia in terms of finals requirement in restorative dentistry. Ideally, all requirements should be similar among institutions and should closely follow the guidelines provided by the MQA. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13352 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.55-62